Analisis Kinerja Keuangan untuk Mengukur Tingkat Kesehatan Koperasi Simpan Pinjam Syariah di Kota Lhokseumawe - Muammar Khaddafi; Novi Apriani (Jurnal EMT KITA, 2021)
This study aims to analyze the soundness level of financial performance at the Sharia Savings and Loan Cooperative in Lhokseumawe City and the cooperative which has the highest financial performance level. The samples of this research are the KPN KOPERISMA Cooperative, the Tunas Baru KPN Cooperative, the Muammalat Sejahtera Employee Cooperative, the Al Ummah Dayah Ulumuddin Islamic Boarding School Cooperative, the Kriya Sakti Cooperative (KOPINKRA), and the KPN Tiga Serangkai Cooperative. The data used are the 2018 financial statements of each cooperative, the method of data analysis used is the assessment of the financial performance of the sharia savings and loan cooperatives. The results showed that: 1) KOPERISMA Cooperative got a score of 77.25 with the predicate Fairly healthy, 2) KPN Tunas Baru Cooperative got a score of 73.55 with the predicate Fairly Healthy.